Magnetic Properties and Magnetocaloric Effect in Layered NdMn1.9Ti0.1Si2 - M.F. Md Din; J.L. Wang; S.J. Kennedy; S.X. Dou (Atom Indonesia, 2014)
The structural and magnetic properties of the NdMn1.9Ti0.1Si2 compund have been studied by high-intensity x-ray and high-resolution neutron powder diffraction, specific heat, dc magnetization, and differential scanning calorimetry measurements over the temperature range of 3-450 K. The Curie temperature and Néel temperature of layered NdMn1.9Ti0.1Si2 are indicated as TC ~ 22 K and TN ~ 374 K respectively. The first order magnetic transition from antiferromagnetic [AFil-type] to ferromagnetic [F(Nd)+Fmc] around TC is found in layered NdMn1.9Ti0.1Si2and is associated with large magnetocaloric effect. This behavior has been confirmed as a contribution of the magnetostructural coupling by using neutron and x-ray powder diffraction. The magnetic entropy change –ΔSM ~ 15.3 J kg-1 K-1 and adiabatic temperature change ΔTad ~ 4.7 K have been determined using magnetization and specific heat measurement under 0-5 T applied fields. This compound exhibits almost no thermal and magnetic hysteresis, thus potentially applicable in low temperature region for magnetic refrigerator material.Received: 31 December 2013; Revised:10 February 2014; Accepted: 24 February 2014